2010
DOI: 10.1152/japplphysiol.00780.2009
|View full text |Cite
|
Sign up to set email alerts
|

Associations of polymorphisms of eight muscle- or metabolism-related genes with performance in Mount Olympus marathon runners

Abstract: Athletic endurance performance is probably partly under genetic control, but genetic association studies have yielded inconclusive results. The objective of the present study was to evaluate the association of polymorphisms in eight muscle- or metabolism-related genes with endurance performance in participants of the Olympus Marathon running race. We recruited 438 athletes who participated in the 2007 and 2008 annual running events of the Olympus Marathon: a 43.8-km race with an ascent from sea level to 2,690-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 44 publications
0
53
0
1
Order By: Relevance
“…Our own investigation from the model in ELSA suggested a detectable difference from around 55 years. Fewer investigations have been reported on the associations between APOE and measures of physical performance; however, findings include no association with athletic performance (Tsianos et al 2010) and associations between ε4 and slower gait speeds from a study of 1,262 adults aged over 65 years (Melzer et al 2005). Our larger investigation found evidence to support a role of APOE in decline in walk speeds over a 4-year period in one study but little evidence for associations with physical capability from cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our own investigation from the model in ELSA suggested a detectable difference from around 55 years. Fewer investigations have been reported on the associations between APOE and measures of physical performance; however, findings include no association with athletic performance (Tsianos et al 2010) and associations between ε4 and slower gait speeds from a study of 1,262 adults aged over 65 years (Melzer et al 2005). Our larger investigation found evidence to support a role of APOE in decline in walk speeds over a 4-year period in one study but little evidence for associations with physical capability from cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Wolfarth et al [43] reported that the 16Arg allele was overrepresented in 313 white male elite endurance athletes compared to 297 white male sedentary controls, suggesting a positive association between the tested Gly16Arg polymorphism and endurance performance. Furthermore, in a study of 316 Mount Olympus marathon runners, Tsianos et al [44] have shown an association between the 16Arg allele and the fastest time of athletes. The results of these studies are in agreement with the previous work in which an association of the 16Arg allele with higher peak VO 2 in heart failure patients was reported [45].…”
Section: Ace I Allelementioning
confidence: 97%
“…The same negative results were obtained by Sawczuk et al [62] and Grenda et al [63] in two studies involving 334 endurance athletes from Russia and Poland. Furthermore, Tsianos et al [44] have reported an excess of the TT genotype of the BDKRB2 gene rs1799722 C/T polymorphism in 316 male Mount Olympus marathon runners.…”
Section: Bdkrb2 29 and Rs1799722 T Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsianos et al (2010) evaluated the association of polymorphisms in eight muscle-or metabolism-related genes with endurance performance in 438 participants of the Olympus Marathon running race. Eleven polymorphisms were evaluated.…”
Section: Do Polymorphisms Of Muscle or Metabolism-relatedmentioning
confidence: 99%